Pomodoro Technique for lecturers' productivity / Rozianiwati Yusof ... [et al.]. - Yusof, Rozianiwati; Mohd Yunus, Sri Yusmawati; Abdul Rahman, Normaziah; Hashim, Norhafizah; Aziz Fadzillah, Nor Azlina (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Pomodoro Technique is an effective time management strategy that can significantly enhance lecturers' productivity. Lecturers can focus intensely for 25-minute intervals, known as 'Pomodoros', and followed by short 5-minute breaks (Sheldon & Wigmore, 2022). This technique helps minimize distractions and sustain a high level of focus. Moreover, it not only helps in managing time effectively but also reduces delayed action and allows for more efficient task completion (Kaplan & Courtney, 2023). Additionally, lecturers can also combine time blocking with the Pomodoro technique to allocate specific time slots for their tasks, enhancing productivity even further. Besides that, this technique also supports goal setting, enabling lecturers to define clear and measurable objectives, which can increase motivation and a sense of accomplishment as they move closer to their targets. Furthermore, by adopting the Pomodoro Technique, lecturers can boost their academic productivity, resulting in improved research output and teaching effectiveness.